Research on Safety Risk, Prevention and Control in Port Dangerous Goods Container Yard. Issue 1 (May 2021) - Xie, Tiansheng; Lu, Xin; Wang, Guobo; Lin, Feng
Abstract: Based on the analysis of the storage, safety risks and risk factors of the dangerous cargo container yard in the port, the accident hazards and the scope of impact were evaluated through simulation calculations. The results show that the main risk factors are inherent dangerous characteristics of dangerous goods, improper storage modes, substandard packaging, and the failure to implement the main responsibility of the port operator, the weak safety awareness of employees, the inadequate safety supervision and the improper emergency response. The influence range extends as far as the surrounding regions. It is necessary to take countermeasures such as limiting the stockpile, equipping with safety facilities, and strict management to prevent and control risks and accidents.